Mapping the English Proficiency Used by Junior High School English Teachers across Riau Province - Syarfi, Muhammad; Ras, Fakhri; Masyhur, Masyhur (Proceedings of the UR International Conference on Educational Sciences, 2018)
The second phase of the research highlights the speaking ability of English language teachers at the junior high school level in Riau Province, with the aim of getting a concrete picture of English Proficiency, especially the ability to speak English. The subject of this study was 180 junior high school level teachers in Riau Province. All research subjects become the research sample. The instrument of this study is a recording of the activities of using English in classroom learning activities by junior high school English teachers throughout Riau Province. The collected data were analyzed to describe the speaking ability of the teachers based on 7 factors namely gender, employment status, level of education, tertiary education, length of service, frequency of participation in training activities as well as ethnicity. From gender factors, female teachers have better abilities than male teachers. From the employment factor, teachers of the Civil Servants have a slightly better ability than teachers who are Non-Civil Servants. Furthermore, the speaking ability based on the level of education, shows that the higher the level of education, the better the speaking ability of the English teachers. In terms of tertiary institutions, it turns out that PTN graduates have better speaking skills than PTS graduates. In terms of length of teaching period, it is known that teachers who have served 21 s.d 30 years have the best speaking ability, followed by those whose teaching period 11 s.d 20 years.